Circular Polarization of the Square, Circular, Triangle, and Hexagonal Microstrip Antenna - Nurhayati Nurhayati; Paulen Aulia Lutfia; Raimundo Eider Figueredo Sobrinho; Alexandre Manicoba de Oliveira; JoÃ£o Francisco Justo Filho; Takeshi Fukusako (INAJEEE (Indonesian Journal of Electrical and Electronics Engineering), 2020)
Microstrip antenna with circular polarization can be applied for many applications. Some microstrip antenna with square, circular, triangular, and hexagonal shape has been designed to get return loss, axial ratio, and radiation performance. We compare twelve microstrip antenna by maintaining its substrate dimension, feeding shape, and outer patch dimension. Even though antenna has a circular patch, it doesnt always produce circular polarization. From the simulation, we found that with add some structure, the antenna can reach multiband resonance from 1 to 6 GHz. The Circular patch antenna reached seven numbers of the multiband resonance frequency. The hexagonal patch antenna reaches the highest directivity as 9.53 dBi. The circular polarization is achieved for a square and Hexagonal patch shape with axial ratio value is 1.96 dB at 4 GHz and  1.26 dB at 4.1 GHz sequentially at phi 900 and theta 900.